2007
DOI: 10.1007/s11274-007-9592-3
|View full text |Cite
|
Sign up to set email alerts
|

Sago starch as a low-cost carbon source for exopolysaccharide production by Lactobacillus kefiranofaciens

Abstract: Low-cost sago starch was used as a carbon source for production of the exopolysaccharide kefiran by Lactobacillus kefiranofaciens. A simultaneous saccharification and fermentation process of sago starch for kefiran production was evaluated. Factors affecting the process such as an initial pH, temperature, starch concentration, including a mixture of a-amylase and glucoamylase were determined. The highest kefiran concentration of 0.85 g/l was obtained at the initial pH of 5.5, temperature of 30°C, starch concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…The maximal kefiran production (0.83 g L −1 ) was obtained at sucrose concentration of 20 g L −1 after 72 h. Further increase in the concentration of sucrose did not highly increase the production of kefiran. These results were in accordance with those obtained by Yeesang et al (2008), where they reported that further increase in reducing sugar concentration above the optimal concentration does not significantly increase kefiran production. This can be explained on the basis that the concentrations of sucrose higher than 20 g L −1 may restrict the ability of cells to uptake sucrose, thus inhibiting the biosynthesis of kefiran.…”
Section: Resultssupporting
confidence: 93%
“…The maximal kefiran production (0.83 g L −1 ) was obtained at sucrose concentration of 20 g L −1 after 72 h. Further increase in the concentration of sucrose did not highly increase the production of kefiran. These results were in accordance with those obtained by Yeesang et al (2008), where they reported that further increase in reducing sugar concentration above the optimal concentration does not significantly increase kefiran production. This can be explained on the basis that the concentrations of sucrose higher than 20 g L −1 may restrict the ability of cells to uptake sucrose, thus inhibiting the biosynthesis of kefiran.…”
Section: Resultssupporting
confidence: 93%
“…Although microbial amylases are generally active at ambient temperatures of up to 60 °C (Yeesang et al. 2008), the optimal temperature for the cell growth and kefiran production from lactose by Lactobacillus kefiranofaciens , which is responsible for kefiran production (Yeesang et al. 2008), was the same as found for kefiran production during this study.…”
Section: Resultssupporting
confidence: 54%
“…The highest content of kefiran was obtained at the same temperature as the kefir grains growth ( Τ = 30 °C). Although microbial amylases are generally active at ambient temperatures of up to 60 °C (Yeesang et al. 2008), the optimal temperature for the cell growth and kefiran production from lactose by Lactobacillus kefiranofaciens , which is responsible for kefiran production (Yeesang et al.…”
Section: Resultsmentioning
confidence: 99%
“…In earlier studies, concentrations of a-amylase (different from that used in our study) ranging from 0.19 [17] to 1 g/L [18] were used for the production of kefiran and L-lactic acid from starches. The activity of a-amylase solution may reach 160 units/L when a-amylase concentrations as low as 0.19 g/L are used.…”
Section: Resultsmentioning
confidence: 99%